2001
DOI: 10.1034/j.1399-3062.2001.003001002.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of bronchoalveolar lavage following renal transplantation

Abstract: Organ transplant recipients are at high risk of infectious pulmonary complications. In this retrospective study, the diagnostic yield of bronchoalveolar lavage (BAL) was evaluated in renal transplant recipients. The results were analysed in special regard to the clinical presentation of pulmonary infections and the possible impact of new immunosuppressive agents. Over a 5-year period 91 BAL were performed in 71 renal transplant recipients. Microorganisms were isolated from 69% of BAL (63/91): bacteria 32%; cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 17 publications
(25 reference statements)
2
21
0
2
Order By: Relevance
“…Atypical patterns are often found in patients with diabetes or in renal transplant recipients [30]. However, REICHENBERGER et al [31] have previously reported a very low incidence of TB in immunocompromised patients. Between 42 and 86% of patients with pulmonary TB may be symptomatic [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Atypical patterns are often found in patients with diabetes or in renal transplant recipients [30]. However, REICHENBERGER et al [31] have previously reported a very low incidence of TB in immunocompromised patients. Between 42 and 86% of patients with pulmonary TB may be symptomatic [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…This procedure has been used extensively as a diagnostic procedure in transplant recipients with suspected pulmonary infections, especially opportunistic infections. 3,4 Candida and Aspergillus species are the most important causes of invasive fungal infections in solid-organ transplant recipients, and are associated with almost 100% mortality. 1,5 In most studies, the infection started during the first 6 months after transplant.…”
Section: Discussionmentioning
confidence: 99%
“…11 Similar results were reported in the study of Reichenberger and coworkers, who evaluated the diagnostic yield of BAL in renal transplant recipients; microorganisms were isolated from 69% BAL cases, but most were bacterial and viral, and Aspergillus was detected only in 1 case. 3 Hohenadel and associates 12 investigated the role of BAL in 95 immunocompromised patients who had hematologic disorders with pneumonia. Pathologically relevant isolates were observed in 65% cases; BAL provided the definitive diagnosis in only 29 cases (31%), and 11% of these infections were fungal.12 In a study by Al-Za'abi and coworkers in immunosuppressed patients (96% lung transplant recipients), the most common identified organism was Aspergillus species, and 17% Aspergillus cases were detected by BAL cytologic examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die diagnostische Ausbeute der Bronchoskopie beträgt in Studien mit immunkompromittierten Patienten unterschiedlicher Provenienz 56 bis 72% [38,39]. Bei neutropenischen Patienten, die zum Zeitpunkt der Untersuchung meist unter einer breiten empirischen Antibiotikatherapie stehen, liegt die Ausbeute niedriger.…”
Section: Bronchoskopieunclassified